The trail from quantum electro dynamics to informative medicine. (June 2015) - Foletti, Alberto; Ledda, Mario; Grimaldi, Settimio; D'Emilia, Enrico; Giuliani, Livio; Liboff, Abraham; Lisi, Antonella
Abstract Several years ago just before Christmas, in a small meeting room at the Institute of Pharmacology at the University of Rome, we had the opportunity to attend a meeting on "The role of QED in medicine" by Emilio Del Giudice and Giuliano Preparata. Before that meeting, we were more oriented towards a mechanistic view of Biochemistry and Medicine, believing that chemical reactions could only take place when a random collision between molecules with a gain in energy takes place. We envisioned water as just a solvent in which was possible to dissolve a solute. After we listened to Giuliano's and Emilio's speech on the "New physics of water", and on "The possible origin of coherence in cell, tissues and the interaction of very weak and low frequency magnetic fields with the ions, systems of the cell", we realized that living organisms are complex electrochemical systems which evolved in a relatively narrow range of well-defined environmental parameters. Environmental natural electro-magnetic fields are an ubiquitous factor in nature. If nature gave certain organisms the ability to receive information about the environment via invisible electromagnetic signals, then there must also the capability to discriminate between significant and meaningless ones. Bearing in mind that electromagnetic fields can be perceived by living organisms by means a resonance effect, we should not be amazed if they can be able to induce different biological effects. The work that we will present in memory of Emilio is based on the hypotheses that an aqueous system a chemical differentiation agent such as retinoic acid (RA) were electronically captured and transferred to the culture medium of Neuroblastoma Cell Line (LAN-5) and the proliferation rate was assessed to assess cell responses to the electromagnetic information transfer through the aqueous system. Like those enfolded in living organisms could play a synergic role in modulating biological functions, generating dissipative structures under appropriate patterns of electromagnetic signals providing basis for storing and retrieving biological activities. An external electro-magnetic stimulus from a source molecule can be stored, translated, and transferred by the aqueous systems to the biological target, selectively driving their endogenous activity and mimicking the effect of a source molecule.